Countries' perceptions of China's Belt and Road Initiative: A big data analysis - Alicia García Herrero; Jianwei Xu (Bruegel, 2019)
Drawing on a global database of media articles, we quantitatively assess perceptions of China's Belt and Road Initiative (BRI) in different countries and regions. We find that the BRI is generally positively received. All regions as a whole, except South Asia, have a positive perception of the BRI, but there are marked differences at the country level, with some countries in all regions having very negative views. Interestingly, there is no significant difference in perceptions of the BRI between countries that officially participate in the BRI and those that do not. We also use our dataset of media articles to identify the topics that are most frequently associated with the BRI. The most common topics are trade and investment. Finally, we use regression analysis to identify how the frequency with which these topics are discussed in the news affects the perceptions of the BRI in different countries. We find that the more frequently trade is mentioned in the media, the more negative a country's perception of the BRI tends to be. On the other hand, while investment under the BRI seems also to attract attention in the media, it is not statistically relevant for countries' perceptions of the BRI.
Keywords: 330